Perceived daylight conditions in multi-family apartment blocks – Instrument validation and correlation with room geometry. (February 2020) - Bournas, Iason; Dubois, Marie-Claude; Laike, Thorbjörn
Abstract: This article investigates the relation between subjective evaluations and objective measurements of daylighting in multi-family residential buildings. More specifically, the suitability of an observer-based environmental assessment (OBEA) instrument to assess indoor daylight conditions was tested in a field study conducted in six typical multi-family apartment buildings in the central and metropolitan area of Malmö (Latitude: 55.6 °N), Sweden. The OBEA used self-administered questionnaires based on bipolar semantic scales aiming to capture two perceived daylight qualities: brightness and distribution. Following a factorial approach, one component pertaining to perceived brightness was deducted ("Brightness", Cronbach's alpha = 0.89) and validated by associating it with outdoor global horizontal irradiance (Spearman's rS = 0.566, p = 0.006), which was monitored during the survey. Subsequently, this component was correlated with key geometric attributes of the investigated apartments to highlight the most important associations between perceived brightness and room geometry. Results indicate that the OBEA displays high internal reliability for the derived component, and is fit for daylight perception evaluations in residential spaces. In addition, the analysis showed a tendency for variables pertaining to window size to associate with perceived brightness, but also contributing to this association was the level of global horizontal irradiance. Highlights: An observer-based assessment tool for daylight in apartments was evaluated. Field study for 225 rooms was performed by use of semantic differential scales. Factor analysis identified one dimension for perceived brightness, Brightness. Brightness correlated with global horizontal irradiance (r = 0.566, p = 0.006). Geometry pertaining to window size correlated more strongly with Brightness.